Impact of repos and reverse repos on interest rates: Evidence from Nepal - Risal, Hari Gopal; Karki, Dipesh (The journal of contemporary issues in business and government, 2019)
Repos and reverse repos are popular money market management tools used by the Central Bank of Nepal especially to manage liquidity crunc hes and surpluses which may arise from time to time. However, the evidence of the actual impact of these tools in correcting the money market is somewhat contested. This paper investigates the impact of repos and reverse repos on interbank borrowing rates in the Nepalese market using a longitudinal data set from 2007 to 2016. The paper uses an iterative approac h for identifying the best model to explain the phenomenon. The main finding of this research is that the money market maturity period of repos is more signific ant in reducing interest rates during a liqui dity crunc h rather than the volume of repos issued. Further, the research also finds that reverse repos are not signific ant enough to mop-up excess liquidity in the market. These findings can provide guidelines for monetary policy in Nepal, insofar as the issuance of repos and revers e repos is concerned.